Comparison of Child Development Between Aterm and Premature Birth at Age 2-3 Years Old - Innas Tiara Ardhiani (Jurnal Keperawatan Muhammadiyah, 2019)
Objective: Premature births are at risk of developing language delays, motor balance and coordination. This study aims to analyze developmental differences in children with a history of premature birth and term. Methods: The data used was primary data  through  filling  questionnaires  and  interviews  to  subjects.  This  study  was  observational analytic  with  retrospective  cohort  design.  The  population  was  all 2-3 years old children at Kabupaten Probolinggo. Sampling was using a simple sampling formula and obtained 100 children  into  2  groups.  First  group  was  50 children  who  aterm at birth.  Second  group  was  50 children  who  premature at birth.  Result: The result showed that there were there is significant different at child development between aterm and premature born childen  (p<0.05). The  relative risk (RR) analysis  showed  that  the value is significant enough. Children development  was influenced  by  type  of  born (RR=1.647x) Conclusion: The development of 2-3 years old children is very important, especially children with a history of premature birth who have a risk of developmental disorders. Parents should give more attention in providing appropriate developmental stimulation according to the child's age.